Down-regulation of cytochrome P450 1A1 by monomethylarsonous acid in human HepG2 cells. (15th March 2017) - Elshenawy, Osama H.; Abdelhamid, Ghada; Soshilov, Anatoly A.; Denison, Michael S.; El-Kadi, Ayman O.S.
Highlights: Inorganic arsenic trivalent metabolite, MMA(III) inhibits CYP1A1 through an AhR-dependent mechanism. MMA(III) inhibits nuclear accumulation of AhR. MMA(III) does not bind to AhR ligand binding site. MMA(III) inhibits CYP1A1 through a post-translational mechanism. MMA(III) increases ROS production. Abstract: Inorganic arsenic is a human toxicant and carcinogen that has been extensively studied over decades; however, no definitive understanding of the underlying mechanisms has been established yet. Arsenic is capable of modulating the expression of aryl hydrocarbon receptor (AhR)-regulated genes, nevertheless, whether its trivalent organic metabolites have similar effects or not need to be investigated. Therefore, in this study we examined the effects of monomethylarsonous acid (MMA(III)) as compared to its parent compound sodium arsenite (As(III)) on the expression of CYP1A1 in HepG2 cells. HepG2 cells were treated with MMA(III) (5 μM) or its parents compound, As(III) (5 μM), in the absence and presence of the prototypical AhR ligand, 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD; 1 nM). Experiments were conducted at 6 h for gene expression; 24 h for XRE-driven luciferase activity, protein expression, and EROD activity. Our results showed that both MMA(III) and As(III) decreased CYP1A1 mRNA, protein, and catalytic activity levels; and inhibit the TCDD-mediated induction of CYP1A1 mRNA, protein, and catalytic activity levels. MMA(III) and As(III) significantly inhibited XRE-driven luciferase activity and it inhibited the TCDD-mediated induction of XRE-driven luciferase reporter gene expression. Although MMA(III) and As(III) were not shown to be AhR ligands, both compounds showed inhibition of nuclear accumulation of AhR transcription factor as evidenced by immunocytochemical analysis. MMA(III) and As(III) had no effect on CYP1A1 mRNA stability; however MMA(III), but not As(III), decreased the protein stability of CYP1A1. As(III), but not MMA(III), induced HO-1 mRNA levels. Both MMA(III) and As(III) increased ROS production. Our results demonstrate for the first time that, MMA(III) down-regulates CYP1A1 mainly through transcriptional and post-translational mechanisms. This modulation of CYP1A1 proves that trivalent metabolites of arsenic are highly reactive and could participate in arsenic toxicity.